2019
DOI: 10.1101/841957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gli1+ mesenchymal stromal cells modulate epithelial metaplasia in lung fibrosis

Abstract: Highlights• Gli1+ MSCs are required for metaplastic airway progenitor differentiation into KRT5+ basal cells.• Hedgehog activation of MSCs promotes KRT5 differentiation of airway progenitors by suppressing BMP activation.• Restoring BMP activation attenuates metaplastic KRT5 differentiation• Metaplastic KRT5+ basal cells in human fibrotic lungs demonstrate altered BMP activation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Unlike MRC5 cells, AHLM cells placed in 3D organoids upregulate a group of secretory products that antagonize BMP signaling and downregulate HHIP, an inhibitor of sonic hedgehog (SHH) signaling. BMP signaling is known to promote murine AEC2 differentiation whereas SHH signaling favors differentiation of murine epithelial progenitors to KRT5+ basal cells by promoting BMP antagonism (Cassandras et al, 2019;Wang et al, 2018). The addition of HHIP or BMP4 to the 3D organoid co-cultures attenuates airway differentiation and maintains hAEC2 lineage, consistent with a causal impact of altered BMP and SHH signaling on hAEC2 fate.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Unlike MRC5 cells, AHLM cells placed in 3D organoids upregulate a group of secretory products that antagonize BMP signaling and downregulate HHIP, an inhibitor of sonic hedgehog (SHH) signaling. BMP signaling is known to promote murine AEC2 differentiation whereas SHH signaling favors differentiation of murine epithelial progenitors to KRT5+ basal cells by promoting BMP antagonism (Cassandras et al, 2019;Wang et al, 2018). The addition of HHIP or BMP4 to the 3D organoid co-cultures attenuates airway differentiation and maintains hAEC2 lineage, consistent with a causal impact of altered BMP and SHH signaling on hAEC2 fate.…”
Section: Discussionmentioning
confidence: 71%
“…2A). We and others have previously shown that secreted BMP antagonists are upregulated in the mesenchyme of IPF lungs (Adams et al, 2019;Cassandras et al, 2019;Koli et al, 2006;Myllarniemi et al, 2008) (Fig. S3A), where ectopic basal cells appear in the alveoli accompanied by the loss of hAEC2s.…”
Section: Haec2-intrinsic and Niche Factors Altered In Ipf Modulate Mementioning
confidence: 76%
“…In mouse following severe H1N1 influenza infection, rare Trp63+ basal progenitor cells, or lineage negative epithelial progenitors (LNEPs), can give rise to alveolar Krt5+ pods which act as an emergency response to re-establish barrier in the lung (Xi et al, 2017;Yang et al, 2018). In mouse following bleomycin injury, Trp63+ basal cells contributed less efficiently to alveolar Krt5+ pods than Scgb1a1 creERT2 lineaged cells (Cassandras et al, 2020).…”
Section: Resourcementioning
confidence: 99%
“…Regenerative potential: Secretory cells can self-renew and differentiate into ciliated cells during mouse airway development, homeostasis, and airway epithelium injury repair (Rock et al, 2009). Following severe lung injury such as bleomycin-induced damage, both Sox2 creERT2 -lineaged cells and Scgb1a1 creERT2 -lineaged cells can give rise to a small percentage of AT1 and AT2 cells, as well as Krt5+ pods in the alveolar region (Yuan et al, 2019;Cassandras et al, 2020). As the common cell type that is lineage traced by both of these cre lines is secretory cells, these results suggest that secretory cells can give rise to a minority of alveolar epithelial cells following bleomycin-induced injury.…”
Section: Secretory Cellsmentioning
confidence: 99%
See 1 more Smart Citation